2018
DOI: 10.1159/000487154
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors: Are They a Real Threat to the Patient?

Abstract: Background: Proton pump inhibitors are among the most frequently prescribed drugs in the world and are generally considered safe. However, there is growing concern regarding their safety. Summary: A nonsystematic review of the current literature was performed regarding proton pump inhibitors and their adverse effects. Proton pump inhibitors seem to be associated with fundic gland polyp development (without clinical relevance) and Clostridium difficile infection. Also, in cirrhotic patients, their prescription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
4
0
2
Order By: Relevance
“…Moreover, use of PPIs may also increase risk of falls [ 291 , 292 , 293 ]. These associations, however, have not been confirmed in a number of longitudinal studies and reviews [ 259 , 280 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 ]; even a modest reduction in fracture risk with PPI use has been reported [ 307 , 310 ]. Some researchers who are not supporting the association of PPI therapy with BMD recognize, nevertheless, that in PPI users the risk of fractures and falls could be higher [ 311 , 312 ] as the unadjusted HR was significantly elevated (1.36, 95% CI 1.19–1.55).…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…Moreover, use of PPIs may also increase risk of falls [ 291 , 292 , 293 ]. These associations, however, have not been confirmed in a number of longitudinal studies and reviews [ 259 , 280 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 ]; even a modest reduction in fracture risk with PPI use has been reported [ 307 , 310 ]. Some researchers who are not supporting the association of PPI therapy with BMD recognize, nevertheless, that in PPI users the risk of fractures and falls could be higher [ 311 , 312 ] as the unadjusted HR was significantly elevated (1.36, 95% CI 1.19–1.55).…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…A diminuição da produção do ácido clorídrico, induzida pelos IBPs, limita absorção do cálcio e causa uma perturbação na microbiota comensal, predispondo a um risco aumentado para perda de massa óssea, fraturas e de infeção por Clostridium difficile; são ainda descritas, a deficiência na absorção de alguns nutrientes, atrofia gástrica, risco aumentado para neoplasia gástrica, pneumonia e lesão renal. [64][65][66] É com base nestas evidências que os critérios de Beers de 2015 consideram inapropriada a prescrição regular dos IBPs, por mais de oito semanas, exceto em doentes com risco elevado 1,48 ; critérios que justificam o elevado número de MPIs identificados no estudo, bem como, na generalidade das instituições de longa permanência para idosos. 7,11,66 Face a estes resultados, considera-se importante a adoção de estratégias interdisciplinares 50 para assegurar a otimização do regime medicamentoso da pessoa idosa institucionalizada, tais como: intervenções educacionais, revisão da medicação, conferências de caso e utilização de programas informáticos que suportem a decisão clínica 67,68 ; no processo de revisão da medicação, devem ser envidados todos os esforços para minimizar o uso de fármacos, com particular atenção para aos grupos farmacológicos mais problemáticos, conforme explanado nos parágrafos anteriores.…”
Section: Discussionunclassified
“…[64][65][66] É com base nestas evidências que os critérios de Beers de 2015 consideram inapropriada a prescrição regular dos IBPs, por mais de oito semanas, exceto em doentes com risco elevado 1,48 ; critérios que justificam o elevado número de MPIs identificados no estudo, bem como, na generalidade das instituições de longa permanência para idosos. 7,11,66 Face a estes resultados, considera-se importante a adoção de estratégias interdisciplinares 50 para assegurar a otimização do regime medicamentoso da pessoa idosa institucionalizada, tais como: intervenções educacionais, revisão da medicação, conferências de caso e utilização de programas informáticos que suportem a decisão clínica 67,68 ; no processo de revisão da medicação, devem ser envidados todos os esforços para minimizar o uso de fármacos, com particular atenção para aos grupos farmacológicos mais problemáticos, conforme explanado nos parágrafos anteriores. 67,68 Apesar das discussões acerca dos benefícios económicos, diretos e indiretos, obtidos através da descontinuação de MPIs na população idosa, 21,[31][32][33]42 persiste alguma divergência nos valores apresentados, relacionada com a economia e o sistema de saúde de cada país, o grau de comparticipação dos medicamentos e o preço utlizado para valor de cálculo.…”
Section: Discussionunclassified
“…It has been shown that the effects of histamine type 2 receptor blockers weaken over time. Moreover, the usage of proton pump inhibitors is limited due to their side effects such as osteoporotic fracture, vitamin B12/magnesium/iron deficiencies, anemia and dementia 4,5 . Correction of the imbalance between aggressive and protective factors in the gastrointestinal mucosa is the basis of ulcer treatment.…”
Section: Introductionmentioning
confidence: 99%